Penerapan Penggunaan Sosial Media Instagram Sebagai Media Promosi Dalam Meningkatkan Penjualan Pada Ayam Keprabon - Fadilah, Nur; Junaidi, M. Rofiq (Journal of Economics and Business Research (JUEBIR), 2025)
This study aims to explore the use of social media, specifically Intagram, as a promotional tool to enchase the sales of Ayam Keprabon products. Given the intense competition in the Surakarta market, this research seeks to identify effective promotional strategies and utilize Intagram’s features, such as Stories and collaboration with influencers. The research methodology employed includes interviews with informants from Ayam Keprabon and qualitative data analysis. The findings indicate that the application of Instagram as a promotional medium can significantly increase sales by employing strategies such as buy one get one promotions. This research is expected to provide practical recommendations for business owners in leveraging social media to optimize sales and build their brand.